The Pitch Lake. Brighton. Trinidad. B.W.I. 451 No.17 - (:unkn) unknown (My University, 2010)
In this antique postcard one sees a close up view of the surface of the Pitch Lake which looks like an elephant’s skin. Gullies on its surface are filled with rainwater and have fine grasses growing in them and there is a fringe of forest trees on the horizon. A few oil derricks rise above their canopy at right horizon.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Brighton; Cities and towns--Trinidad and Tobago--La Brea; Asphalt industry--Trinidad and Tobago; Pitch; Forests and forestry--Trinidad and Tobago; Oil well drilling rigs--Trinidad and Tobago; Trees--Trinidad and Tobago; [1910]; Pitch Lake, The (La Brea)